THE CONCEPT OF AN INCLUSIVE ADAPTATION MODEL IN HIGHER EDUCATION (International journal of artificial intelligence, 2026)
This scientific article provides a comprehensive analysis of the issue of adapting students with disabilities to an inclusive educational environment in the higher education system as a pressing pedagogical problem. The theoretical and methodological foundations of the concept of an inclusive adaptation model are examined based on axiological, systemic, competency-based, and learner-centered approaches. The structural components of the model, pedagogical conditions for its implementation, and the experience of foreign higher education institutions are analyzed in depth. Based on the research findings, scientific conclusions and practical recommendations aimed at improving the inclusive adaptation model for the national higher education system have been developed.